Cracks in the JD-R model? The failure of strengths use, job crafting, and home-work spillover to support wellbeing during COVID-19 - van Zyl, Llewellyn Ellardus; Cornelisse, Menno A.; Le Blanc, Pascale; Rothmann, Sebastiaan (Frontiers in Psychology, 2025)
Drawing from the Job Demands-Resources (JD-R) model, this study examined the relationship between job characteristics, work-home interference, motivation, and psychological wellbeing during the COVID-19 lockdown. Specifically, it explored whether individual-level strategies such as strengths use, job crafting, and home-work regulatory factors (i.e., positive and negative home-work spillover) moderated these relationships. A cross-sectional survey of 522 participants was conducted during the lockdown. Structural equation modelling, mediation, and moderation analyses tested the proposed relationships. Results showed that work overload, organizational support, and job security were significantly associated with both negative and positive work-home interference, while growth opportunities and advancement were not. Positive and negative work-home interference and motivation were directly linked to psychological wellbeing, although only positive work-home interference was associated with motivation. Further, strengths use and job crafting moderated was only found to moderate the relationship between job security and negative work-home interaction. Finally, home regulatory practices may not be helpful in explaining how job characteristics affect the work-home relationship. The findings suggest that during crises, the JD-R model falls short in accounting for the complex interaction between job characteristics and employee outcomes. While structural factors like work overload, organizational support, and job security remain central, individual strategies and home-regulatory practices had limited impact. These insights challenge assumptions about the JD-R model's “universal applicability” and the presumed effectiveness of personalized coping strategies during systemic disruption. It also exposes a deeper limitation of the JD-R model: its implicit tendency to pathologize the employee by placing the burden of wellbeing on individuals rather than addressing the systemic conditions that shape it. In times of crisis, the onus should not be on employees to adapt, but rather on organizations to create environments that support work-life balance and sustainable wellbeing.